2019
DOI: 10.1016/j.nicl.2019.101711
|View full text |Cite
|
Sign up to set email alerts
|

Detecting frontotemporal dementia syndromes using MRI biomarkers

Abstract: BackgroundDiagnosing frontotemporal dementia may be challenging. New methods for analysis of regional brain atrophy patterns on magnetic resonance imaging (MRI) could add to the diagnostic assessment. Therefore, we aimed to develop automated imaging biomarkers for differentiating frontotemporal dementia subtypes from other diagnostic groups, and from one another.MethodsIn this retrospective multicenter cohort study, we included 1213 patients (age 67 ± 9, 48% females) from two memory clinic cohorts: 116 frontot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 61 publications
(102 reference statements)
3
35
2
3
Order By: Relevance
“…Here, using structural MRI, we detected an extensive pattern of brain volume loss in TDP-43 Q331K knockin mice, a preclinical model for ALS-FTD, while still at an early stage of disease. Significantly, many of the brain areas affected in mutant mice are analogous to those involved in patients with FTD (Meeter et al, 2017;Bruun et al, 2019). Similar regions have also been implicated in recent studies of patients with ALS .…”
Section: Discussionmentioning
confidence: 62%
“…Here, using structural MRI, we detected an extensive pattern of brain volume loss in TDP-43 Q331K knockin mice, a preclinical model for ALS-FTD, while still at an early stage of disease. Significantly, many of the brain areas affected in mutant mice are analogous to those involved in patients with FTD (Meeter et al, 2017;Bruun et al, 2019). Similar regions have also been implicated in recent studies of patients with ALS .…”
Section: Discussionmentioning
confidence: 62%
“…However, a recent machine learning study of dementia patients in two European memory clinics (N=1,213) showed that only 59% of FTD patients demonstrated a distinct frontotemporal atrophy pattern; the rest showed a subcortical atrophy pattern similar to AD [Bruun et al, 2019]. Further, across all dementia subtypes (including AD and VaD), the highest predictive accuracy was achieved using asymmetric frontotemporal atrophy to distinguish PPA and bvFTD subtypes, and temporal pole volume to distinguish the fluent and nonfluent PPA subtypes (85% AUC for both analyses) [Bruun et al, 2019]. These findings may reflect sex differences that are inherent to male-dominant bvFTD subtype, and a female-dominant nonfluent PPA subtype, but further work is needed to interpret these results.…”
Section: Frontotemporal Dementiamentioning
confidence: 99%
“…8, 9), while a voxelbased morphometry study [41] showed evidence of metabolic and atrophic changes in the bilateral frontal and temporal lobes in FTD patients, whereas the affected regions of metabolism are more severe and larger than those of atrophy in the frontal and temporal lobe. Further, detecting FTLD using MRI atrophy biomarkers, derived from normalized volumes by automated calculation of the anterior versus posterior index, the asymmetry index, and the temporal pole left index, was reported to provide additional diagnostic assessment and assist in diagnosing FTLD in clinical practice [42].…”
Section: Bvftdmentioning
confidence: 99%